2018
DOI: 10.1152/ajpendo.00316.2017
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of postprandial glucose fluxes in response to acute and chronic endurance exercise in healthy humans

Abstract: The effect of endurance exercise on enhancing insulin sensitivity and glucose flux has been well established with techniques such as the hyperinsulinemic clamp. Although informative, such techniques do not emulate the physiological postprandial state, and it remains unclear how exercise improves postprandial glycaemia. Accordingly, combining mixed-meal tolerance testing and the triple-stable isotope glucose tracer approach, glucose fluxes [rates of meal glucose appearance (Ra), disposal (Rd), and endogenous gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 51 publications
1
17
2
1
Order By: Relevance
“…Postprandial blood glucose and insulin were similar between the 24 h post-exercise and no-exercise control conditions. This contradicts previous reports of improved insulin sensitivity in the days following acute exercise in healthy individuals (Mikines et al 1988;Brestoff et al 2009;Ortega et al 2015;Morrison et al 2018). However, Bogardus et al (1983) reported a similar finding where the insulin-sensitizing effects the day after exercise are absent when participants are fed 100 g of glucose 3 h post-exercise.…”
Section: Discussioncontrasting
confidence: 77%
See 3 more Smart Citations
“…Postprandial blood glucose and insulin were similar between the 24 h post-exercise and no-exercise control conditions. This contradicts previous reports of improved insulin sensitivity in the days following acute exercise in healthy individuals (Mikines et al 1988;Brestoff et al 2009;Ortega et al 2015;Morrison et al 2018). However, Bogardus et al (1983) reported a similar finding where the insulin-sensitizing effects the day after exercise are absent when participants are fed 100 g of glucose 3 h post-exercise.…”
Section: Discussioncontrasting
confidence: 77%
“…However, Bogardus et al (1983) reported a similar finding where the insulin-sensitizing effects the day after exercise are absent when participants are fed 100 g of glucose 3 h post-exercise. In light of previous findings (Bogardus et al 1983), the high-glucose ingested 3 h post-exercise in the current study may have led to faster and more complete glycogen replenishment compared to other studies where habitual meal regimes are resumed after exercise (Morrison et al 2018). Additionally, and in contrast to others (Ortega et al 2015;Morrison et al 2018), we also observed an elevation in postprandial NEFAs and fat oxidation 24 h post-exercise, a possible result of the preceding 3 h post-exercise trial which may have also precluded improvements in 24 h postprandial glucose and insulin.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…Indeed, postprandial insulin sensitivity as calculated from the OGIS and PREDIM, which have been validated and correlate with clamp-derived measures of whole-body insulin sensitivity (33), was >20% higher than after the BCAA + diet. This improvement could have resulted from increased insulin-mediated glucose disposal, which mainly occurs in skeletal muscle under these conditions (46). Alternatively, EGP could have been decreased under BCAA-depleted conditions owing to lower substrate supply for hepatic gluconeogenesis (47).…”
Section: Discussionmentioning
confidence: 99%